Pemenuhan Hak-Hak Korban Kekerasan Dalam Rumah Tangga (Studi Pada Polres Kepulauan Aru) - Dominggus Steven Djilarpoin; Sherly Adam (Faculty of Law Pattimura University, 2021)
Introductioan: Victims of domestic violence can exercise their rights as mandated in the PKDRT Law so that they can assist the police in smoothing the legal process that is handled and cooperation between the Police and related agencies and the victims themselves is needed in order to minimize cases of domestic violence that occur. so far according to the children of the PKDRT Law.Purposes of the Research: This study aims to analyze and discuss the fulfillment of the rights of victims of domestic violence at the Aru Islands Police This type of research is normative juridical. Methods of the Research: This study uses a normative juridical method. The problem approach used is the statutory approach, concept analysis approach and case approach. Legal materials use primary legal materials and secondary legal materials. The technique of collecting legal materials is through literature study and qualitative analysis of legal materials. Results of the Research: Fulfillment of the rights of victims of domestic violence carried out by the Aru Islands Police has been in accordance with Law Number 23 of 2004 concerning the Elimination of Domestic Violence, in Article 10 which explains the rights given to victims of violence in household, namely providing protection for victims. The protection provided includes medical services for victims, cooperating with social institutions related to legal assistance and assistance, conducting socialization on domestic violence, providing spiritual guidance services. The Aru Islands Police have implemented and fulfilled the rights of victims of domestic violence, but in the fulfillment of their rights, there are still obstacles faced by both the Police and the victims themselves, where the victims do not fully use the rights of the victims as mandated in the The PKDRT Law.